The proto CpG island methylator phenotype of sessile serrated adenomas/polyps. Issue 10 (2nd November 2018) - Parker, Hannah R.; Orjuela, Stephany; Martinho Oliveira, Andreia; Cereatti, Fabrizio; Sauter, Matthias; Heinrich, Henriette; Tanzi, Giulia; Weber, Achim; Komminoth, Paul; Vavricka, Stephan; Albanese, Luca; Buffoli, Federico; et al.
ABSTRACT: Sessile serrated adenomas/polyps (SSA/Ps) are the putative precursors of the 20% of colon cancers with the CpG island methylator phenotype (CIMP). To investigate the epigenetic phenotype of these precancers, we prospectively collected fresh-tissue samples of 17 SSA/Ps and 15 conventional adenomas (cADNs), each with a matched sample of normal mucosa. Their DNA was subjected to bisulfite next-generation sequencing to assess methylation levels at 2.7 million CpGs located predominantly in gene regulatory regions and spanning 80.5Mb; RNA was sequenced to define the samples' transcriptomes. Compared with normal mucosa, SSA/Ps and cADNs exhibited markedly remodeled methylomes. In cADNs, hypo methylated regions were far more numerous (18, 417 vs 4288 in SSA/Ps) and rarely affected CpG islands/shores. SSA/Ps seemed to have escaped this wave of demethylation. Cytosine hyper methylation in SSA/Ps was more pervasive (hypermethylated regions: 22, 147 vs 15, 965 in cADNs; hypermethylated genes: 4938 vs 3443 in cADNs) and more extensive (region for region), and it occurred mainly within CpG islands and shores. Given its resemblance to the CIMP typical of SSA/Ps' putative descendant colon cancers, we refer to the SSA/P methylation phenotype as proto-CIMP . Verification studies of six hypermethylated regions in an independent series of precancers demonstrated DNA methylation markers' high potential for predicting the diagnosis of SSA/Ps and cADNs. Surprisingly, proto-CIMP in SSA/Ps was associated with upregulated gene expression; downregulation was more common in cADNs. In conclusion, the epigenetic landscape of SSA/Ps differs markedly from that of cADNs. These differences are a potentially rich source of novel tissue-based and noninvasive biomarkers.